'Sauvé du déluge des jours' : Taxidermy, photography and literature in Adrien Goetz and Karen Knorr's Le Soliloque de l'empailleur. (February 2015) - Collington, Tara L.
This paper examines the intersection of photography and literature in Le Soliloque de l'empailleur, a short story by Adrien Goetz which reproduces 12 images from photographer Karen Knorr's Fables . After discussing the profoundly intertextual nature of Knorr's photos, which are inspired by Aesop, La Fontaine and Ovid, I undertake a close reading of Goetz's story, examining the shared themes concerning the art of taxidermy and the disjunction between nature and culture present in both works. I also examine the ways in which the text evokes Knorr's Fables, as the narrator sometimes describes a specific photo and at other times encourages the reader to imagine a photo that is not reproduced. The shared thematic content between Goetz's story and Knorr's photos, and the intermedial interaction between text and image allow the reader to concretise the fictional universe of the museum of taxidermied animals envisaged by both partners in this photo-literary collaboration.